2013
DOI: 10.3892/ol.2013.1481
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the EGF gene intronic polymorphism, rs2298979, and colorectal cancer

Abstract: Colorectal cancer (CRC) is an important disorder that results from genetic and epigenetic alterations in one colonic epithelial cell. Epidermal growth factor (EGF) is critical in the development of tumors in epithelial tissues. Variations in the DNA sequence of the EGF gene may be particularly significant with regard to susceptibility to CRC. The present study aimed to investigate the effect of the EGF gene single nucleotide polymorphism (SNP), rs2298979, on CRC. In this prospective study, 220 samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Analogous EGFR CRMs are likely to exist in mammals, especially because complex interactions between BMP, Wnt, Shh, multiple Dlx paralogs and other factors, are implicated in the induction of FGF signaling in mammalian limb development. Consistent with this idea, specific single nucleotide polymorphisms (SNPs) in humans in non-coding loci of genes encoding EGFR ligands have been shown to be associated with different types of cancer [ 44 46 ]. Such loci may be enhancer elements analogous to vnE and rhoE .…”
Section: Discussionmentioning
confidence: 99%
“…Analogous EGFR CRMs are likely to exist in mammals, especially because complex interactions between BMP, Wnt, Shh, multiple Dlx paralogs and other factors, are implicated in the induction of FGF signaling in mammalian limb development. Consistent with this idea, specific single nucleotide polymorphisms (SNPs) in humans in non-coding loci of genes encoding EGFR ligands have been shown to be associated with different types of cancer [ 44 46 ]. Such loci may be enhancer elements analogous to vnE and rhoE .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on Iranian population investigated the association of rs2298979 polymorphism, located in a noncoding region -intron 1 of EGF gene, with colorectal cancer. A/G genotype carriers were identified as less susceptible than the carriers of A/A genotype [23].…”
Section: Epidermal Growth Factor (Egf) Signaling Pathway and Colorectal Cancermentioning
confidence: 97%
“…In order to discover the pathogenesis, many studies had conducted on various aspects such as genetic, life styles and environment. Recently, some studies indicated the significant association in the genes polymorphisms and CRC risk (Chaleshi et al, 2013;Kassab et al, 2014). NOS3, as one of the key gene, was said to play a key role in cancers and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%